PENINGKATAN HASIL BELAJAR SISWA PADA MATERI KONSEP MOL DENGAN MENERAPKAN MODEL PEMBELAJARAN PROBLEM SOLVING - SITI AMANAH (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2022)
This study aims to improve students' chemistry learning outcomes in the mole concept material by applying the problem solving learning model. The research method used is Classroom Action Research (CAR), which generally consists of 2 (two) cycles. Each cycle has 4 (four) stages namely planning, action, observation, and reflection. This research was conducted in class X IPA1 with a total of 25 students. This study focused on the concept of moles which includes the conversion of the number of moles into the number of particles, the number of masses, the number of volumes, Avogadro's hypothesis, empirical formulas, molecular formulas, levels of substances, and limiting reagents. Data collection techniques used were tests, observation sheets, and student questionnaires. From the results of research in cycle II there was an increase in activity and student learning outcomes from cycle I namely. In cycle II, the average post-test score of students was 77.87 and the percentage of completeness of student learning outcomes reached 88% of students achieving grades ?65. And from the results of student questionnaires and the results of observations on learning using the problem solving model, there were good responses from students. This proves that learning using the problem solving model has a positive impact on students in the teaching and learning process. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar kimia siswa pada materi konsep mol dengan penerapan model pembelajaran problem solving. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang secara umum terdiri dari 2 (dua) siklus. Masing-masing siklus terdapat 4 (empat) tahapan yaitu perencanaan, tindakan, observasi, dan refleksi. Penelitian ini dilaksanakan di kelas X IPA1 yang berjumlah 25 siswa. Penelitian ini difokuskan pada materi konsep mol yang mencakup konversi jumlah mol ke dalam jumlah partikel, jumlah massa, jumlah volume, hipotesis Avogadro, rumus empiris , rumus molekul, kadar zat, dan pereaksi pembatas. Teknik pengumpulan data yang digunakan adalah tes, lembar observasi, dan angket siswa. Dari hasil penelitian pada siklus II terjadi peningkatan aktivitas dan hasil belajar siswa dari siklus I yaitu. Pada siklus II, diperoleh rata-rata nilai post test siswa 77,87 dan persentase ketuntasan hasil belajar siswa mencapai 88% siswa mencapai nilai ?65. Dan dari hasil angket siswa serta hasil observasi terhadap pembelajaran dengan menggunakan model problem solving terdapat tanggapan yang baik dari siswa. Hal ini membuktikan bahwa pembelajaran dengan menggunakan model problem solving memberikan dampak yang positif bagi siswa dalam proses belajar mengajar.